A Study on Factors Causing the Demand-Supply Gap of Affordable Housing - Chan, Alyssa Poh Jzen; Lee, Benny Hai Chim (2016)
The demand-supply gap of affordable housing has been a serious issue in Malaysia and if the issue is not resolved, will exacerbate house ownership and accommodation problems in many urban areas throughout the country.The aim of this study is to explore the factors that cause imbalance distribution of housing due to the increasing need for housing and to propose effective measures to manage the demand-supply gap. Questionaires have been distributed and thirty one feedbacks have been are received from the respondents. Quantitative methodology is utilised to examine the results acquired from the questionnaire. The outcome indicates that the respondents want the government to provide more effort on resolving the housing problem. Therefore, actions ought to be made by the respective parties to correct this issue with a specific end goal to mitigate the shortage in supply of affordable housing.The results of this research conclude that people want the government to monitor the housing industry more effectively, the locations with severe shortage of affordable housings are Kuala Lumpur, Georgetown, Klang Valley and Petaling Jaya and the severity of the affordability of housing market in Malaysia needs to be made aware to the public to prevent further deterioration of the conditions.